Kecerdasan Emosi Dan Dukungan Guru Sebagai Prediktor Resiliensi Akademik Pada Siswa SMK - Andhieni Eka Putri; Tri Na’imah; Nur’aeni; Fatin Rohmah Nur Wahidah (CV. ITTC INDONESIA, 2025)
Vocational High Schools (SMK) are educational institutions designed to prepare students to become skilled professionals in their respective fields. However, the challenges encountered by students can often lead to feelings of pressure, stress, and even a sense of inadequacy. Therefore, academic resilience is essential for students to effectively navigate these demands. This study aims to examine the influence of emotional intelligence and teacher support on the academic resilience of 11th-grade students at SMK X Pemalang. This research employs a quantitative correlational approach, with a sample of 169 students selected through simple random sampling. Data collection was carried out using the Academic Resilience Scale (ARS-30), the Emotional Quotient Inventory: Youth Version (EQ-i:YV), and the Teacher Support Scale (TSS). The data analysis yielded a t-value of 9.862 and an R of 0.368, indicating that emotional intelligence significantly influences academic resilience, contributing 36.8% to the variance. The t-value for teacher support was 2.111, with an R of 0.026, suggesting that teacher support also significantly influences academic resilience, albeit with a smaller contribution of 2.6%. Furthermore, the F-test result of 49.342 and an R of 0.373 indicate that both emotional intelligence and teacher support collectively influence academic resilience, accounting for 37.3% of the variance. The remaining 62.7% is attributed to other unexamined factors, such as self-efficacy and social support.